Modeling and control of quartz crystal operated in liquid for bio-sensing application - A. Kadhim Fahad, Abu Abdullah (2014)
Nowadays the applications of sensors are a very promising research field since they find application in many different areas. Biosensors are an increasingly important technology in the detection of compounds ranging from pesticides to biological weapons. Typically, biosensors consist of a biological macromolecule that is immobilized on the surface of a signal transducer. As the macromolecule binds specifically to the ligand being detected, the signal transducer can measure a physical change due to the binding event. One promising type of detector is the Quartz Crystal Microbalance (QCM). The QCM is a piezoelectric mass-sensing device. A QCM device works by sending an electrical signal through a gold-plated quartz crystal, which causes a vibration at some resonant frequency. The QCM then measures the frequency of oscillation in the crystal. When used as a biosensor, the QCM can detect changes in frequency of the crystal due to changes in mass on the surface of the crystal. In the present work, all related equations and data base related to biosensors piezoelectric devices will be considered in the developed model. The model will describe biosensors limitations and capacities together with measurement resolutions and errors. The work will includes build of software program using Microsoft visual studio C# 2010.net frame work 4.0 and all available theoretical and empirical formulas and program data base will include the data for QCM sensors and resonance frequencies, this program will include all cases needed to be studied for the present work (bio sensing). Many sensors can be used for QCM, the present work will be limited to TSM sensors, and the proposed software for Bio-sensing. The frequency signal is detected by a frequency counter and processed electronically in a separate computer. The QCM sensor used is 19.5 MHZ using buffer media in the testing procedure. The result according to z-methods indicates that while the resonance frequencies increase the small amount of despite material can be easily detected. With the data extracted for (5 MHZ) sensors with effective area of 14 mm2, the results show that as the change in resonance frequency increase as the despite material increase. The film thickness of deposit material increase as the natural frequencies of sensors decreased.